Social Security and Population Ageing in Vietnam: A Guarantee for the Elderly People’s Life - Thanh Dao, Binh; ThiBich Tran, Ngoc; Anzelmovna Barysheva, Galina; Si Tran, Lam (International Journal of Criminology and Sociology, 2022)
Demographic change affects the socio-economic development of any country. In Vietnam, the population and housing censuses from 1989 to 2019 showed an appreciable increasing proportion of the elderly in the total population and fast ageing pace. Older people have many difficulties in their life. Among them, only 27% have pensions or stable incomes, and the rest 73% live without pensions, facing many difficulties. Vietnam is a developing country, and social security policies are in the process of completion. Therefore, improving the social security system, as well as creating opportunities for active ageing and wellbeing for older people, was one of the strategic goals of the Long-Term Development Plan that Vietnam’s government has been carried out for more than half a century. In this article, the issues of demographic change, population ageing, social security system, social assistance and pension benefits as the actual sociological problem are studied by using quantitative methods and comparative analysis approach to confirm the research questions; the proposals made by the authors can be helpful for today’s reforming social security system in Vietnam and social policy making in context of ageing in Vietnam where a large number of elderly people do not have any social benefits.